Structuralist macroeconomics : applicable models for the third world - Taylor, Lance (New York ; Basic Books, 1983)
The options for policy and economic change in developing countries are severely limited by specific and durable structural features of their economies. Offering a comprehensive and coherent macroeconomic theory for developing countries, Taylor develops simple, useful and tested models for different groups of developing countries -- mineral exporters, countries with an important food sector and economies with endemic inflation. While focusing on problems of economic stabilization and policies such as devaluations and interest manipulations, he also considers income distribution and seeks to alter the structural composition of sectoral outputs.
1. The Structuralist Perspective -- 2. Adjustment mechanism- The Real Side -- 3. Adjustment Mechanism- Two-Sector Models -- 4. Short-Run Adjustment in Practice -- 5. Money and Other Assets in the Short Run -- 6. Money, Inflation, and Growth -- 7. Trade balance Complications -- 8. Foreign Assets and the Balance of Payment -- 9. Two-Sector Models of Inflation, Distribution, and Growth -- 10. Trade patterns and Southern Growth -- 11. Policy lessons.
Includes bibliographical references and index.
Keywords: ECONOMIC HISTORY; MACROECONOMICS